Estimating merchantable and non-merchantable wood volume in slash walls using terrestrial and airborne LiDAR - Nicholas Cranmer; Tao Han; Brett Chedzoy; Peter J. Smallidge; Colin Beier; Lucas Johnson; Xiangtao Xu (Forest Ecology and Management, 2024)

Applying Service-Dominant Logic to Peer-to-Peer Experiences Between Master Forest Owner Volunteers and Woodland Owners in New York State - Danielle L. Eiseman; Shorna B. Allred; Peter J. Smallidge (Small-scale Forestry, 2022)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Effects of watershed liming onPicea rubens seedling biomass and nutrient element concentration - Peter J. Smallidge; Donald J. Leopold (Water, Air, & Soil Pollution, 1997)

EFFECTS OF WATERSHED LIMING ON PICEA RUBENS SEEDLING BIOMASS AND NUTRIENT ELEMENT CONCENTRATION - PETER J. SMALLIDGE; DONALD J. LEOPOLD (Water, Air, & Soil Pollution, 1997)